PKM PETANI IKAN LELE DI BANGKINANG KECAMATAN BANGKINANG KABUPATEN KAMPAR - Syafriani; Afiah; Yusmardiansah (Universitas Pahlawan Tuanku Tambusai, 2022)
Kampar Regency is one of the largest fish producers in Riau Province. As a fish-producing area, one of them is catfish. Catfish is very easy to get at a relatively cheap price, so it can be a potential in developing activities into varied and high-value products. Judging from its benefits, catfish is a type of healthy food that is low in calories, a complete source of protein, a source of vitamin B12, and contains healthy fatty acids that are good for consumption by all ages. The purpose of this activity is to assist catfish farmers in increasing fish trading. catfish produced by processing catfish into nuggets, and catfish pop. Catfish processing is expected to improve the economy of catfish farmers because so far catfish are only sold raw to collectors or direct buyers at low prices, while the price of seeds and feed is high. Packaging and marketing of processed catfish products in the hope of improving the welfare of catfish farmers.There are several obstacles faced by partners, namely (1). Procurement of feed, this is because the price of feed continues to increase, making it burdensome for farmers to buy fish feed. The high price of feed causes high production prices, while the selling power of catfish is low. at least the profits obtained by catfish farmers. (2). Capital limitations. (3). The low motivation of catfish farmers to become entrepreneurs with catfish as the main ingredient. (4). There is no diversity of processed catfish products. (5). There is no packaging and marketing of catfish. Activities that will be carried out in this PKM program include several development efforts, including: 1. Providing motivation to catfish farmers to become entrepreneurs. 2. Training or practice of making variations in catfish production, this is done considering that fresh catfish is very abundant in Kampar Regency, but its processing is still very lacking. The product variants that are added are nuggets and catfish pop. 3. Packing or product packaging. Products will be packaged with more attractive packaging. 5. Changes in marketing strategy. Catfish are usually sold by collectors or directly to traditional markets around the Kampar Regency area. This catfish processed product will be sold to stalls, shops or supermarkets, and labeling will make it look attractive. Keywords: Nugget, catfish pop, marketing